Sex differences in the association between prenatal exposure to maternal obesity and hippocampal volume in children. Issue 2 (5th January 2020) - Alves, Jasmin M.; Luo, Shan; Chow, Ting; Herting, Megan; Xiang, Anny H.; Page, Kathleen A.
Abstract: Introduction: Animal studies have shown that male but not female offspring exposed to maternal obesity have abnormal hippocampal development. Similar sex differences were observed in animal models of developmental programming by prenatal stress or maternal diabetes. We aimed to translate this work into humans by examining sex‐specific effects of exposure to maternal obesity on hippocampal volume in children. Methods: Eighty‐eight children (37 boys and 51 girls) aged 7–11 years completed the study. Maternal prepregnancy body mass index (BMI) was obtained from electronic medical records. A high‐resolution anatomical scan was performed using a 3‐Tesla magnetic resonance imaging (MRI) scanner. Total hippocampal volume and hippocampal subfield volumes were analyzed using FreeSurfer 6.0. Linear regression was used to investigate sex differences in relationships between maternal prepregnancy BMI and child hippocampal volume. Results: Maternal prepregnancy BMI ranged from 19.0 to 50.4 kg/m 2 . We observed a significant interaction between maternal prepregnancy BMI and sex on total hippocampal volume ( p < .001) such that boys ( r = −.39, p = .018) but not girls ( r = .11, p = .45) had a significant negative relationship between maternal prepregnancy BMI and total hippocampal volume. This relationship in boys remained significant after adjusting for child and maternal covariates ( β = −126.98, p = .012). The sex interactions with prepregnancy BMI were consistently observed in hippocampal subfields CA1 ( p = .008), CA2/3 ( p = .016), CA4 ( p = .002), dentate gyrus ( p < .001), and subiculum ( p < .001). Conclusions: Our results support findings in animal models and suggest that boys may be more vulnerable to the adverse effects of exposure to maternal obesity on hippocampal development than girls. Abstract : We provide novel evidence in support of findings in rodent models suggesting that in utero exposure to maternal obesity differentially impacts the hippocampus of boys compared to girls during childhood. This is the first study in humans to show changes to the hippocampus in association with in utero exposure to maternal obesity.